Women in Sweden 1981 - family and working life - Statistics Sweden (Statistics Sweden, 1995)
This investigation on Swedish women aged 20-45 years shed light on their views on family and working life. The questions are divided into nine parts: Background describe marital status, household composition, housing, and environment growing up in. Furthermore the women had to state if they agreed or not with a number of statements concerning children and parenthood. Education and occupation dealt with experienced education, plans and desires on further education, time of changing from one occupation to another, attitude toward part-time work, housework and plans on going out to work after parental leave. Gainfully employed were asked questions about time spent travelling to work and working hours. Questions about pregnancy and child bearing dealt with if the pregnancy was planned, if she had to wait for a long time, if the child was wanted, if it was born at a suitable time, and if any pregnancy had been broken. The part concerning birth control dealt with the use of different contraceptives. Present cohabiting include questions about marriage and cohabiting, when moving together, and if one is married with the man one lives together with. Women cohabiting with a man, but not married to him, were asked if they were planning to get married later. Other questions dealt with the distribution of the housework, partner´s occupation and education. To get a summary of periods in her life when living together with a man, there were also a number of questions about earlier cohabiting. Women having children were asked a number of questions about child day-care child day-care used, monthly cost, and if there had been any problems in connection with the use of child day-care. There were also questions asked about the father using the possibility of parental leave, possibilities to get a baby-sitter outside of the family, who stays at home when the child gets ill, and the division of the practical work with the children among the parents. Leisure and economy deals with leisure-time activities, number of evenings she and her partner respectively spends away from home, number of weekends she and her partner respectively spends away from home. Questions about economy deals with the economical standard of the family, and if there at any opportunity had been difficult to settle running expenses. The concluding part deals with future child bearing, if one plans to have (more) children in the future, and the reason to have/not have children.

Denna undersökning av svenska kvinnor i åldrarna 20-45 år belyser deras syn på familj och arbetsliv. Frågorna delades in i nio avsnitt: Bakgrundsavsnittet beskriver civilstånd, hushållets sammansättning, bostad och uppväxt. Dessutom fick kvinnorna ange om de instämde eller ej i ett antal påståenden om barn och föräldraskap. Utbildning och sysselsättning behandlar bland annat vilken utbildning som genomgåtts, planer på och önskemål om ytterligare utbildning, tidpunkter då man övergått från en sysselsättning till en annan, inställning till deltidsarbete, sköta hushåll och planer på förvärvsarbete efter föräldraledighet. Förvärvsarbetande fick frågor om tidsåtgång för arbetsresor, arbetstidens längd och förläggning. Avsnittet om graviditeter och barnafödande tar bland annat upp om graviditeten var planerad, om man fick vänta länge, om barnet var önskat, om det föddes vid en lämplig tidpunkt och om man haft en eller flera avbrutna graviditeter. Födelsekontrollavsnittet behandlar användning av olika preventivmetoder. Avsnittet om nuvarande samboendeförhållande innehåller frågor om äktenskap och samboende, när man flyttade ihop, hur länge man haft stadigt sällskap innan man flyttade ihop och om man är gift med den man sammanbor med. Ej gifta sammanboende fick frågan om man tror att man så småningom kommer att gifta sig. Andra frågor gällde arbetsfördelningen i hemmet, make/sammanboendes sysselsättning och utbildning. För att få en översikt över de perioder i sitt liv kvinnan bott ihop med en man ställdes även ett antal frågor om tidigare samboendeförhållande. Kvinnor med barn fick ett antal frågor om barnomsorg. Vilken form av barntillsyn man använder eller använt sig av, utgift per månad för barntillsyn och om det varit några problem i samband med barntillsynen. Andra frågor tog upp om barnets far utnyttjat möjligheten att vara föräldraledig, möjligheter att ordna barnvakt utanför hushållet, vem som stannar hemma om barnet blir sjukt och föräldrarnas fördelning av det praktiska arbetet med barnet. Avsnittet fritid och ekonomi behandlar fritidsaktiviteter, hur många kvällar i månaden man själv resp. sammanboende är borta hemifrån och antal veckoslut per år man själv resp. sammanboende är borta hemifrån. Frågor om ekonomi gällde familjens ekonomiska standard och om man vid något tillfälle haft svårt att klara de löpande utgifterna. Det avslutande avsnittet tar upp framtida barnafödande, om man planerar att skaffa (fler) barn i framtiden och anledningar till att skaffa resp. inte skaffa barn.
Kvinnor i Sverige 1981 - om familj och arbetsliv
Keywords: housing; boende; occupations; yrken; employment; anställning; family environment; familjemiljö; leisure time; fritid; children; barn; housework; hushållsarbete; marriage; äktenskap; domestic responsibilities; hushållsansvar; child care; barnomsorg; income; inkomst; educational background; utbildningsbakgrund; employment history; anställningshistorik; marital status; civilstånd; parent attitude; föräldraattityd; subsidiary employment; bisyssla; overtime; övertid; pregnancy; graviditet; childbirth; barnafödsel; abortion; abort; contraceptive devices; preventivmedel; spouses; makar; marital history; äktenskapshistoria; paternity leave; pappaledighet; household budgets; hushållsbudget; households; hushåll; commuting; pendling; birth control; födelsekontroll; hours of work; arbetstid; still-birth; dödfödsel; miscarriage; missfall; Reproductive health; Fortplantningshälsa; Employment; Sysselsättning; Gender and gender roles; Kön och könsroller; Family life and marriage; Familjeliv och äktenskap; Children; Barn; Social Sciences; Samhällsvetenskap; Sociology; Sociologi